2018
DOI: 10.1111/inr.12471
|View full text |Cite
|
Sign up to set email alerts
|

Construction and usability of community health nursing database in rural north‐eastern Thailand

Abstract: 515-523Introductions: Digitization could be incorporated in rural areas of resource-poor countries because information gathered by nurses working on-site could be better used. Background: For effective management of community health information, the usage and maintenance of digital records are important. Digitization of information provides essential information for informing health policy. Aim: To develop a sustainable database to effectively collect and manage community health information and nursing practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Like China, the health information management systems in many low-and middle-income countries are fragmented and often include multiple vertical systems designed to meet the requirements of the national government or international organizations/donors. As a result, similar problems occur in other low and middle-income countries (2,17,(22)(23)(24)(25)(26)(27)30). For example, in Indonesia, the reporting forms in each health center are different, which results in missing data and hampers the data standardization process (2,17,30).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Like China, the health information management systems in many low-and middle-income countries are fragmented and often include multiple vertical systems designed to meet the requirements of the national government or international organizations/donors. As a result, similar problems occur in other low and middle-income countries (2,17,(22)(23)(24)(25)(26)(27)30). For example, in Indonesia, the reporting forms in each health center are different, which results in missing data and hampers the data standardization process (2,17,30).…”
Section: Discussionmentioning
confidence: 98%
“…Research on Indonesia found that its private health sector hardly reports TB cases, as required by its national health legislation (22). Similarly, there is also evidence that India, Namibia, and Thailand all suffer from a lack of national data standardization and accessibility (22)(23)(24)(25)(26)(27)(28), and might not accurately report the number of confirmed TB cases. It is also reasonable to assume that many other low-and middle-income countries without high functioning health information management systems could face similar problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Thailand, health-promoting hospitals were placed within approximately 10,000 inhabitants; and community health nurses (CHNs) were employed 19 ) , who are key personnel in community health programs. Their activities are focused on health promotion and disease prevention, such as maternal and child health, prevention of lifestyle-related diseases, and infectious disease control.…”
Section: Discussionmentioning
confidence: 99%